Biomechanical differences of foot-strike patterns during running: A systematic review with meta-analysis^ - Almeida, M. O.; Davis, I. S.; Lopes, A. D. (Journal of Orthopaedic & Sports Physical Therapy, 2015)
Objectives: To determine the biomechanical differences between foot-strike patterns used when running.